Optimization of a hierarchical system of inventory management products aircraft - Мачалін, І.О. (Proceedings of National Aviation University (archive), 2007)
Hierarchical classification of possible variants of construction of the control of inventories of wares of aviation technique systems is made. An index is developed for the estimation of efficiency of the system. The choice of optimum variant of control of inventories is made.